Penerapan Strategi Pembelajaran Aqidah Akhlak Untuk Penguatan Karakter Religius Siswa - Adi Rosadi; Siti Zahra Tsania Rahmah; Melati Novalita Putri; Nenah Haryati (Pascasarjana IAIN Ponorogo, 2025)
The development of religious character in students remains a central challenge in Islamic education, particularly at the madrasah level. This study aims to describe and analyze the implementation strategy of Aqidah Akhlak (Islamic Creed and Morals) learning at MTs Al Atiqiah and its impact on strengthening students' religious character. Using a qualitative case study approach, data were collected through participatory observation, in-depth interviews, and documentation studies over three months. The research findings indicate that the integration of three main approaches religious habituation through daily prayers and Qur'an recitation, teacher exemplarity in attitude and behavior, and contextual learning linking Islamic values to social realities proved highly effective in shaping students' religious character. The study revealed a significant increase in consistency of worship, improved moral behavior, and active participation in religious-social activities among students. These results demonstrate that a systematic and integrative learning strategy can successfully internalize religious values within the madrasah environment, offering a comprehensive model for Islamic character education that balances traditional and contextual approaches.